“ITU PILIHAN TERBAIK!”: MEMAHAMI PERSEPSI WANITA TERHADAP TUBEKTOMI - Fatmawati, Riswi Alinda; Sari, Atriany Nilam; Argaheni, Niken Bayu; Sukamto, Ika Sumiyarsi; Putri, Noviyati Rahardjo (Jurnal Sains Kebidanan, 2024)
Background: The participation of women as tubectomy acceptors in Indonesia is only 4.2%. Various factors play a role in decision making, this is also influenced by each woman's perception regarding tubectomy. Objective: To explore women's perceptions of tubectomy and their relationship to factors that influence decision making regarding tubectomy selection. Method: Qualitative research, phenomenological study using in-depth interviews with 8 informants at the Colomadu I Community Health Center. Informants were recruited using a linear snowball sampling technique. The findings were processed using NVivo version 12 Plus software inductively with analysis techniques according to Miles, et al. Results: Informants gave various statements regarding perceptions of tubectomy, including tubectomy as a contraceptive solution, permanent, effective in terminating pregnancy, permitted in Islam, economical, safe, easy to use and comfortable. The reasons behind the informants' desire to use tubectomy were varied, such as parity, husband's role, obstetric history, and age. Conclusion: All informants have a positive perception of tubectomy from the perspective of procedure, law, costs, and advantages of tubectomy. People closest to you, such as husbands and friends, are important when considering decision making. Health workers as the front guard have an equally important role in forming positive perceptions of tubectomy.